Demographic Situation of the Czech Republic – The Current Situation and the Main Goals for the Future - Adrian Moliński (Studia Europejskie, 2019)
The main aim of the article is to analyze the demographic situation of the Czech Republic and to present the prospects for Czech demography in the coming years. The text is divided into sections related to the most important components of the demographic situation - population size and factors that influenced it in the past (e.g. the baby boom phenomenon), live births, the structure of the aging society in the Czech Republic ( there are more people aged 65+ than in the age group 0-14), deaths (causedlargely by cancer and cardiovascular diseases). An important part of the analysis is the problem of external migration. The article was prepared on the basis of data from the Statistical Yearbook (Statisticka Rocenka Česke Republiký), published by Český Statistický Úřad (CSU). The text ends with conclusions and recommendations on demography. The author believes that the demographic problems of the Czech Republic are part of the overall demographic problems of the European Union, such as the low fertility rate (TFR), which is still far from the simple replacement of the generations. The result is an ageing European population, which will have a negative impact on the economy, social systems and external policies.